Inventory Management and Reorder Point (ROP) Strategy Using ABC Analysis Methods in Textile Manufacture - Teuku Faisal Umry; Moses Laksono Singgih (IPTEK Journal of Proceedings Series, 2019)
Tight competition encourages textile companies to increase their competitiveness to efficient in all fields, especially by reducing material stock to its optimum figures without disrupting production operations. Currently this textile manufacture has implemented SAP as an Enterprise Resource Planning (ERP) software. SAP is currently used as Material Resources Planning (MRP), purchasing and inventory control software. Purchases are made automatically using Reorder Point (ROP) and inventory control using the ABC analysis method. In time being there is no relationship between the ABC analysis method to inventory control and ROP. With this condition, the purchase order for material is raised when the stock level is lower than ROP even these unnecessary, causing the stock to become slow moving and dormant when it reaches six months laying on the warehouse and causing excess inventory. This study aims to design and implement how the ABC method can be used to determine purchasing decisions and which ROP calculations should be used. The ABC multi criteria analysis in this study shows that ABC categorization is acceptable for deciding ROP determination. This method of inventory management has the potential to reduce inventory levels up to 17% and eliminate dormant and slow moving